Does mentoring matter: results from a survey of faculty mentees at a large health sciences university - Feldman, Mitchell D. (Medical Education Online, 2010)
BACKGROUND: To determine the characteristics associated with having a mentor, the association of mentoring with self-efficacy, and the content of mentor–mentee interactions at the University of California, San Francisco (UCSF), we conducted a baseline assessment prior to implementing a comprehensive faculty mentoring program. METHOD: We surveyed all prospective junior faculty mentees at UCSF. Mentees completed a web-based, 38-item survey including an assessment of self-efficacy and a needs assessment. We used descriptive and inferential statistics to determine the association between having a mentor and gender, ethnicity, faculty series, and self-efficacy. RESULTS: Our respondents (n=464, 56%) were 53% female, 62% white, and 7% from underrepresented minority groups. More than half of respondents (n=319) reported having a mentor. There were no differences in having a mentor based on gender or ethnicity (p≥0.05). Clinician educator faculty with more teaching and patient care responsibilities were statistically significantly less likely to have a mentor compared with faculty in research intensive series (p<0.001). Having a mentor was associated with greater satisfaction with time allocation at work (p<0.05) and with higher academic self-efficacy scores, 6.07 (sd = 1.36) compared with those without a mentor, 5.33 (sd = 1.35, p<0.001). Mentees reported that they most often discussed funding with the mentors, but rated highest requiring mentoring assistance with issues of promotion and tenure. CONCLUSION: Findings from the UCSF faculty mentoring program may assist other health science institutions plan similar programs. Mentoring needs for junior faculty with greater teaching and patient care responsibilities must be addressed.